Maqashid Sharia Analysis of Islamic Business Offensive Marketing: A Case Study of Rabbani - Wiryanto, Fadhli Suko; Kusuma, Airlangga Surya; Widodo, Purwanto; Atmadja, Hafizh Fadhilah; Arkaan Sunyoto, Muhammad Faturrohman (JURNAL EKONOMI SYARIAH, 2023)
Background: Businesses that carry out Islamic marketing must carry out their marketing activities in accordance with Islamic values, such as providing halal products, serving consumers honestly and fairly, and avoiding promotional activities that are deceptive (tadlis), On the other hand, often companies carry out marketing activities that are not in accordance with Islamic values, such as offensive marketing. Offensive marketing is a marketing activity that is controversial and offensive to certain groups of people.Purpose of Study: Analyze the Offensive Marketing carried out by Rabbani and its relation to the maqasid of sharia.Design/Methodology/Approach: This research is a qualitative descriptive research.Findings: In adopting Rabbani's offensive marketing strategy, companies must ensure that their actions are aligned with the Islamic principles and values embodied in the Sharia Maqasid. This involvesadherence to the principles of ethics, justice, halal, consumer protection, and the good of society in general. Taking into account the maqasid of sharia, i.e. ad-dharuriyah al-khamsa Islamic businesses can use offensive marketing as a tool to achieve sustainable and responsible growth.Types of Papers: Research Articles